PENGARUH MODEL PROBLEM BASED LEARNING DAN CONCEPT MAPPING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Nur Fadillah, - (2018)
PENGARUH MODEL PROBLEM BASED LEARNING DAN CONCEPT MAPPING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR.;--Critical thinking is one of the 21st century skills that needs to be developed. This skill is one of the most important basic capital for everyone and can affect his life in the future. This study aims to determine the effect of using problem-based learning model and concept mapping to the students' critical thinking skills in grade IV in social studies subject on natural resource content. To know the improvement of students' critical thinking skill, the quasi experimental study was done by using the pretest-posttest two treatment design, where in the experimental class 1 used the problem based learning model and the experimental class 2 using concept mapping model. The subjects of the study were the fourth graders of public elementary school number 11 Guguak VIII Koto and nmber 04 Guguak VIII Koto, in Lima Puluh Kota district, West Sumatera, which consisted of 42 people divided into 2 classes, each class consisted of 21 students. The result of statistical parametric calculation with difference test of two mean of independent sample t-test shows that there is no significant difference in the improvement of critical thinking skills among students using problem based learning model with students using concept mapping model. So, it can be concluded that from the results of this study both the model of problem-based learning and concept mapping can be used to improve students' critical thinking skills, because both models are equally effective in improving critical thinking skills.